2017
DOI: 10.2174/1381612823666170616081256
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine Like Receptor-1 (CMKLR-1) Receptor: A Potential Therapeutic Target in Management of Chemerin Induced Type 2 Diabetes Mellitus and Cancer

Abstract: Chemerin is one of the markers that may involve in development of both cancer and insulin resistance. Chemokine like receptor- 1 (CMKLR-1) receptor that regulates chemerin levels exhibits a potential therapeutic target for insulin resistance, type 2 diabetes and cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 87 publications
2
26
0
1
Order By: Relevance
“…Chemerin, a recently discovered adipokine [55] (also known as tazarotene-induced gene 2 (TIG2) and retinoic acid receptor responder 2 (RARRES2) [31]) is a 163 amino acid pre-proprotein that is secreted as a 143 amino acid (18 kDa) proprotein and subsequently undergoes C-terminal cleavage [32,33]. It has recently been discovered that chemerin has at least three receptors: G protein-coupled receptor CMKLR1 (chemokine-like receptor 1 or ChemR23), G protein-coupled receptor 1 (GPR1) and (C-C motif) receptor-like (CCRL) 2 [56][57][58]. CMKLR1 is expressed mainly in adipose tissue (higher levels in white compared to brown adipose tissue), bone, lung, brain, heart, and placenta [55,59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemerin, a recently discovered adipokine [55] (also known as tazarotene-induced gene 2 (TIG2) and retinoic acid receptor responder 2 (RARRES2) [31]) is a 163 amino acid pre-proprotein that is secreted as a 143 amino acid (18 kDa) proprotein and subsequently undergoes C-terminal cleavage [32,33]. It has recently been discovered that chemerin has at least three receptors: G protein-coupled receptor CMKLR1 (chemokine-like receptor 1 or ChemR23), G protein-coupled receptor 1 (GPR1) and (C-C motif) receptor-like (CCRL) 2 [56][57][58]. CMKLR1 is expressed mainly in adipose tissue (higher levels in white compared to brown adipose tissue), bone, lung, brain, heart, and placenta [55,59].…”
Section: Discussionmentioning
confidence: 99%
“…Chemerin plays a role in adipogenesis [6,8,29,55,56,62], preadipocyte differentiation, adipocyte development and metabolism [29,31,57,[63][64][65], insulin sensitivity [6,56], and in lipid and glucose metabolism [29,55,58,66,67]. It is a pro-inflammatory agent [8,16,33,55,65], a chemoattractant for various types of cells [8,16,33,64,65], and modulates immune system function [31,56].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the lipid metabolism, chemerin also influences the dysregulation of glucose metabolism. Supporting the important roles of chemerin in systemic lipid and glucose metabolism, accumulating clinical data indicate that local and/or circulating chemerin levels are increased in patients with obesity, diabetes and cardiovascular disease ( Perumalsamy et al . 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, to our knowledge, studies in humans examining the association between T2DM macroangiopathy and chemerin are lacking. Perumalsamy et al [13] reported that a high chemerin level in humans is considered a marker of insulin resistance (IR) and insulin storage, as well as of T2DM. Chemerin plays a role in both inflammation and metabolism and may provide a link between chronic inflammation and obesity and its related disorders.…”
Section: Introductionmentioning
confidence: 99%